Pengaruh Konseling Tentang Terapi Obat Tbc Terhadap Kepatuhan Penderita Tbc Paru Pada Terapi Obat Periode Februari-Mei 2007 Di Kelurahan Pancoran Mas-Depok - Husnawati, Husnawati; Andrajati, Retnosari; Harianto, Harianto (Majalah Ilmu Kefarmasian, 2007)
The objective of this study was to know the patients’ characteristics, antituber-culosis drug use, and to analyzed the influence of counselling about tuberculosis therapy on patient’s adherence in Pancoran Mas-Depok. This study was quasi experiment design (non randomized control group pretest-postest design). The in-clusion criteria were the people with tuberculosis who took antituberculosis drugs from February – May 2007 in Pancoran Mas-Depok, and followed pretest and postest. Total samples were fifty two respondents. Respondents were divided into two groups, intervention group and control group. Both of groups were given questionnaire (pre-test). After that, intervention group were given counselling about tuberculosis therapy. A month later, both of groups were given a similar questionnaire (postest). Data was analysed with t-test. The result of this study showed that majority of respondents in intervention and control group were productive aged, low education, employee, but majority of intervention group were women and majority of control group were men. The results of this study showed that there was a significant different of adherence to tuberculosis therapy between intervention group and control group (p value = 0,007). There was influence of conselling on patient’s adherence to tuberculosis therapy.